Development Of A Real-Time Embedded Remote Triggering And Monitoring System - Chui, Yew Leong (2003)
The Internet has become the latest medium for communication with advanced features such as file transfer, transaction application, advertising and much more. Recently, quite a number of Internet applications related to remote triggering and monitoring system have been developed. The integration of Internet technology and embedded system concept provides a way for the development of Network Embedded System. In this case, various types of electrical or electronic appliances can be connected to the Network Embedded System to obtain network-connectivity or Internet-ready functionality. For system development purpose, SC12 from BECK-IPC is selected for Network Embedded System implementation. The ideal system can be built with improved diagnostic features and flexibility in terms of configuration parameters. So, this research will cover intelligent system design,protocol stack implementation and manipulation techniques, and embedded system development in details. A real-time embedded remote triggering and monitoring system has been developed. This project is an integration of three systems: Network Embedded System (NBS), Local Connectivity System Toolkit (LCS) and client-side application. NBS provides network connectivity features to LCS and ready to be triggered and monitored by remote clientside application. So, electrical or electronic appliances can be attached to LCS for network/Internet connectivity purpose. On the other hand, client-side application provides a user-friendly Graphic User Interface (GUI) to enhance the usability of the system.